Producing Biogas from Difference Mixing Ratio of Local Pig’s Waste to Produce the Methane Gas in Highest Volume: https://doi.org/10.69692/SUJMRD0802298 - SOULISOMBOON, Dee; SENGPASEUTH, Bouthamaly; SIPHAXAY, Khamphoungeun; SISOMPHOU, Somphan; MANIVANH, Nouphone; BINTHAVONE, Amphaphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This research aimed to investigate the appropriate mixing ratio of local pig waste and water to produce biogas. The pigs were fed with a mixture of bran and boiled Colocasia. This research included four mixture samples in each 3 kg in different total solid (TS) mixing ratios as S1 (TS = 5%), S2 (TS = 6%), S3 (TS = 8%), and S4 (TS = 10%). The mixtures were mixed pig waste and water with ratios of 1:2.5, 1:2, 1:1.5, and 1:1. The total retention time was 60 days. The results showed the PH on average was 7.00-7.15. The appropriate retention time was day 30. The mixture that produced the highest CH4 were S3, S4, S2, and S1 in 68.5, 61, 37.4, and 23.5%VOL, for the H2S and CO2 results varied by the TS. The highest values of H2S at 1329, 1137, 45, and 21 ppm and the highest value of CO2 at 33.57%Vol, 30,68, 19,83, and 17,15 %VOL respectively.